Incomplete Timothy syndrome secondary to a mosaic mutation of the CACNA1C gene diagnosed using next‐generation sequencing. Issue 2 (21st November 2016) - Baurand, Amandine; Falcon‐Eicher, Sylvie; Laurent, Gabriel; Villain, Elisabeth; Bonnet, Caroline; Thauvin‐Robinet, Christel; Jacquot, Caroline; Eicher, Jean‐Christophe; Gourraud, Jean‐Baptiste; Schmitt, Sébastien; Bézieau, Stéphane; Giraud, Mathilde; et al.
Abstract : Autosomal dominant genetic diseases can occur de novo and in the form of somatic mosaicism, which can give rise to a less severe phenotype, and make diagnosis more difficult given the sensitivity limits of the methods used. We report the case of female child with a history of surgery for syndactyly of the hands and feet, who was admitted at 6 years of age to a pediatric intensive care unit following cardiac arrest. The electrocardiogram (ECG) showed a long QT interval that on occasions reached 500 ms. Despite the absence of facial dysmorphism and the presence of normal psychomotor development, a diagnosis of Timothy syndrome was made given the association of syndactyly and the ECG features. Sanger sequencing of the CACNA1C gene, followed by sequencing of the genes KCNQ1, KCNH2, KCNE1, KCNE2, were negative. The subsequent analysis of a panel of genes responsible for hereditary cardiac rhythm disorders using Haloplex technology revealed a recurrent mosaic p.Gly406Arg missense mutation of the CACNA1C gene in 18% of the cells. This mosaicism can explain the negative Sanger analysis and the less complete phenotype in this patient. Given the other cases in the literature, mosaic mutations in Timothy syndrome appear more common than previously thought. This case demonstrates the importance of using next‐generation sequencing to identify mosaic mutations when the clinical picture supports a specific mutation that is not identified using conventional testing. © 2016 Wiley Periodicals, Inc.